The Role of Emotional Response in Mediating the Influence of Green Product and Green Promotion to Sales Performance, A Study on Dairy Products Marketed in Modern Market Channels - Rizal, Moch; Zaenudin, Zaenudin; Rasenda, Rasenda; Ibarda, Aditya; Wiyana, Hari (International Journal of Integrative Sciences, 2024)
This study aims to analyze the role of emotional response in mediating the influence of green products and green promotion on sales performance. This quantitative research with a causality design uses a sample of dairy product customers sold in modern market channels and is analyzed using the Structural Equation Model. The results of the study show that green products and green promotion directly have a positive effect on emotional response and sales performance. Emotional response is proven to affect sales performance and can mediate the influence of green products and green promotion on sales performance. Empirical evidence shows that the implementation of green products and green promotions can increase consumer emotional response and have an impact on improving sales performance. This study implies that the green marketing approach can enhance the integration of environmental issues in all aspects of the company's activities, from strategy formulation, planning, and production to distribution, which positively impacts sales performance. This green marketing concept is very relevant in answering fierce business competition declining global economic conditions and helping companies improve customer service and satisfaction with going green